2022
DOI: 10.3390/su14042318
|View full text |Cite
|
Sign up to set email alerts
|

Swell Conditions at Potential Sites for the Colombian Antarctic Research Station

Abstract: The objective of this paper was to characterize swell conditions in the coastal zone of the South Shetland Islands, where our preliminary analyses evaluated potential locations for the Colombian scientific station. The Simulating Waves Nearshore (SWAN) spectral model was implemented for the Bransfield Strait. The boundary conditions were selected by a cluster analysis of the wave climate from global hindcasting obtained with the WAVEWATCH III model. Some comparisons between the model and wavemeter measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Figure 13, shows that a hybrid system is much more environmentally friendly in many locations of Antarctica. However, in some locations (1,2,3,4,7,8) PV has low necessity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 13, shows that a hybrid system is much more environmentally friendly in many locations of Antarctica. However, in some locations (1,2,3,4,7,8) PV has low necessity.…”
Section: Resultsmentioning
confidence: 99%
“…Conditions in the South Shetland Islands coastal region were characterized in a study evaluating potential locations for the Colombia science station. This study demonstrated the rapid variability of atmospheric conditions in the South Bay with average wind speeds of 4-8 m/s with gusts up to 20 m/s for less than a year [4]. For this reason, wind turbines to be installed in the region should be selected from turbines that are resistant to high-speed winds, even at locations with low average wind speeds.…”
Section: Introductionmentioning
confidence: 95%
“…1B). Wave conditions inside the bay are considered moderate with the prevailing southwest winds (Lonin et al 2022), but winds from northeast, the second common wind direction for the area, can create strong katabatic winds over the bay due to the mountainous relief of the island (Navarro et al 2013;Lonin et al 2022). The average wind speed is 4 ms -1 , Diatoms from two contrasting sites in Antarctica with frequent gusts above 28 ms -1 and peak values above 40 ms -1 (Navarro et al 2013).…”
Section: Study Areamentioning
confidence: 99%
“…The establishment of public programs is essential for the conservation of the city's heritage monuments. In this context, it is crucial that new building materials are developed so that civil construction is more sustainable [11] and that new studies in hostile environments can be carried out [12].…”
mentioning
confidence: 99%